Integrating Geriatric Assessment into Decision-Making after Prostatectomy: Adjuvant Radiotherapy, Salvage Radiotherapy, or None? - Goineau, Aurore; d’Aillières, Bénédicte; de Decker, Laure; Supiot, Stéphane (Frontiers in Oncology, 2015)
Despite current advancements in the field, management of older prostate cancer patients still remains a big challenge for Geriatric Oncology. The International Society of Geriatric Oncology (ISGO) has recently updated its recommendations in this area, and these have been widely adopted, notably by the European Association of Urology. This article outlines the principles which should be observed in the management of elderly patients who have recently undergone prostatectomy for malignancy or with a biochemical relapse following prostatectomy. Further therapeutic intervention should not be considered in those patients who are classified as frail in the geriatric assessment. In patients presenting better health conditions, salvage radiotherapy is to be preferred to adjuvant radiotherapy, which is only indicated in certain exceptional cases. Radiotherapy of the operative bed presents a higher risk to the elderly. Additionally, hormone therapy clearly shows higher side effects in older patients and therefore it should not be administered to asymptomatic patients. We propose a decision tree based on the ISGO recommendations, with specific modifications for patients in biochemical relapse.